Correlation Between Computer Technician Training and Improvement of Hard Skills of Participants at LKP Stimic Ecomtech Jember - Firdauso, Chico Arsyo; Imsiyah, Niswatul; Sintiawati, Nani (Indonesian Journal of Adult and Community Education, 2024)
The aim of this research is to determine the correlation between computer technician training and increasing the hard skills of participants at LKP Stimic Ecomtech Jember. The research method used in this research uses quantitative methods with a correlational type. In this research, the location determination technique uses a purposive area, the research location was carried out at LKP Stimic Ecomtech Jember. After that, respondents are determined using a saturated sample or total sample. Furthermore, the respondents in this study were 30 respondents. Then, the coefficient on the Pearson product moment correlation (r) in this study was obtained at 0.999 (interpretation of a high correlation value). So it can be concluded that there is a correlation between computer technician training and increasing the hard skills of participants at LKP Stimic Ecomtech Jember. This means: The Alternative Hypothesis (Ha) of this research, namely "There is a Correlation Between Computer Technician Training and the Increase in Hard Skills of Participants at LKP Stimic Ecomtech Jember" is accepted in the high correlation category (0.999).